(untitled) (Journal of Governance and Development (JGD), 2018)
This study focused on the studentsâ€™ perception on the strength and weakness of Edmodo Social Learning Platform (ESLP) as well on factors inhibiting active participation of students in forum board. A total of 42 ï¬rst year students of the School of Industrial Technology (SIT), Universiti Sains Malaysia (USM) enrolled for IMK209- Food Physical Properties course were involved in this study. Findings of the study was obtained through the descriptive analysis of the open-ended questionnaire revealed time constraints and technical aspects were found to be the main factors inhibiting the active participation of students in ESLP. The ï¬ndings proved that the ESLP is accepted as a learning platform by the students and able to promote a high level of collaboration and interaction in teaching and learning.